Effects of motivation phase intervention components on quit attempts in smokers unwilling to quit: A factorial experiment. (1st April 2019) - Engle, Jessica L.; Mermelstein, Robin; Baker, Timothy B.; Smith, Stevens S.; Schlam, Tanya R.; Piper, Megan E.; Jorenby, Douglas E.; Collins, Linda M.; Cook, Jessica W.
Highlights: Nicotine gum compared to no gum increased quit attempts by 6 weeks. Patch, when used with behavioral reduction counseling, reduced quit attempts. Aided quit attempts were more likely to produce abstinence than unaided attempts. Abstract: Background: Smoking reduction treatment is a promising approach to increase abstinence amongst smokers initially unwilling to quit. However, little is known about which reduction treatment elements increase quit attempts and the uptake of cessation treatment amongst such smokers. Methods: This study is a secondary analysis of a 4-factor randomized factorial experiment conducted amongst primary care patients (N = 517) presenting for regular healthcare visits in Southern Wisconsin who were unwilling to quit smoking but willing to cut down. We evaluated the main and interactive effects of Motivation-phase intervention components on whether participants: 1) made a quit attempt (intentional abstinence ≥24 h) by 6- and 26-weeks post-study enrollment and, 2) used cessation treatment. We also evaluated the relations of quit attempts with abstinence. The four intervention components evaluated were: 1) Nicotine Patch vs. None; 2) Nicotine Gum vs. None; 3) Motivational Interviewing (MI) vs. None; and 4) Behavioral Reduction Counseling (BR) vs. None. Intervention components were administered over 6 weeks, with an option to repeat treatment; participants could request cessation treatment at any point. Results: Nicotine gum significantly increased the likelihood of making a quit attempt by 6 weeks (23% vs. 15% without gum; p < .05). Conversely, nicotine patch reduced quit attempts when used with BR. Patch also discouraged use of cessation treatment (15.8% vs. 23% without patch; p < .05). Aided vs. unaided quit attempts produced abstinence in 42% vs. 10% of participants, respectively. Conclusion: Nicotine gum is a promising Motivation-phase intervention that may spur quit attempts amongst smokers initially unwilling to quit.